Environmental, Social and Governance (ESG) Initiatives and Firm Efficiency in the Global Tourism and Hospitality Industry: The Role of Business Strategy - Wen-Min Lu; Irene Wei Kiong Ting; Shu-Hsia Huang (Asian Academy of Management Journal of Accounting and Finance, 2025)
This study examines the impact of environmental, social and governance (ESG) practices on firm efficiency in the global tourism and hospitality industry, with a focus on the moderating role of business strategy. Utilising data from 59 firms in the travel, aviation and hotel sectors between 2017 and 2021, the analysis employs the enhanced Russell measure, directional distance function and truncated regression techniques. The findings indicate that the hotel sector outperforms others in both sustainability and market efficiency, while the aviation sector trails due to high energy consumption and disruptions caused by the COVID-19 pandemic. Contrary to the common perception that ESG practices diminish profitability, the results suggest that ESG practices enhance operational efficiency and corporate reputation. Furthermore, business strategy is found to significantly moderate the ESG–efficiency relationship. The study recommends that the aviation sector accelerate the adoption of sustainable aviation fuels, while hotel and travel sectors should continue deepening ESG integration to strengthen long-term resilience and competitiveness.